PELAKSANAAN EDUKASI CUCI TANGAN DALAM PENCEGAHAN RISIKO INFEKSI PADA PERAWAT DI RUANG MAHONI 1 RS BHAYANGKARA TINGKAT I R. SAID SUKANTO JAKARTA - Aulia Afifah Humaira, (2022)
Hospitals have a contribution in providing good health services. Patients who receive treatment while in hospital or other health care facilities are at high risk of getting nosocomial infections which will have an impact on the patient's health condition. The high spread of infection that occurs in health care facilities is caused by nurses' non-compliance in hand hygiene practices. Lack of knowledge is one of the factors causing nurse non-compliance in hand hygiene measures. Efforts that can increase knowledge of nurses are by providing health education related to hand hygiene. This scientific work aims to analyze the effectiveness of hand hygiene education on nurse compliance in preventing the risk of infection in the inpatient ward of the Kramat Jati Police Hospital, Jakarta. The results of this scientific work indicate a change in the attitude of nurses in preventing the risk of infection, namely hand hygiene before and after the intervention. Suggestions to the hospital management team to evaluate the competence of nurses in terms of preventing the risk of infection in accordance with applicable standard operating procedures.